Relationship between Psychological, Subjective and Social Well-Being of Victims of the Armed Conflict in the Municipality of Chalán-Sucre - Hernández , Cindy Henrriquez; Mendivil , Patricia Hernández; Morales , María Alexandra Pinillos; Gómez , Marelis Domínguez; Quiroz , Luis Angel Herazo (Journal of Ecohumanism, 2024)
The objective of this research was to determine the relationship between psychological, subjective and social well-being in victims of the armed conflict in the municipality of Chalán, Sucre. A quantitative approach was used within the positivist paradigm, with a non-experimental design of transversal cohort and correlational scope. The sample consisted of 75 participants, aged between 19 and 80 years, to whom the scales of psychological well-being, subscale of subjective well-being and social well-being were applied. Data analysis included descriptive, frequency and Pearson correlation statistics. The results indicate that autonomy (18.51) is the dimension with the highest mean in psychological well-being, while for social well-being it was social acceptance (20.28). For its part, subjective well-being presents a mean of 74.53. Regarding the relationship, the results show very low correlation values between the three variables, suggesting that there is no significant relationship between them.